CASA Based Assessment of Kangayam bull semen processed with different extenders and Conception rate following AI - Elamurugan, Krishnamoorthy; Selvaraju, Mani; Napolean, Rayappan Ezakial; Ruthrakumar, Ravichandran; Periyannan, Mani; Gopikrishnan, Duraisamy (The Indian Journal of Animal Reproduction, 2023)
Semen extenders are the essential components of cryopreservation of semen. Identification of suitable and ready to  use semen extender is the need of hour for the rapid propagation of Kangayam cows through artificial insemination.  Kangayam bull, aged 5 years was utilized for the study. The semen was collected twice in a week and each time two  ejaculates were collected. A total of 24 ejaculates were utilized for this study. After assessing the general macroscopical  examination the semen was subjected to computer aided semen analysis (CASA) for assessing the kinematic parameters  in fresh diluted semen, pre freeze and post thawed such as sperm motility, progressive individual motility, VAP, VSL, ALH  and LIN were analyzed using CASA. Among all the three extenders, the sperm kinematic parameters during fresh diluted,  pre freeze and post thawed semen stages were higher in group III (liposome based extender) followed by group I (TEYG)  and in group II (soya bean lecithin based extender). Among the three extenders used, the components of liposome based  extender was better and it was able to maintain the structural integrity, plasma membrane integrity and motility in the  sperms of the frozen thawed semen than the other two extenders (TEYG and soya bean lecithin based extenders). Further  the fertility rate was evaluated by the in vivo insemination of 60 Kangayam cows after 12 hours of onset of estrum. The  fertility rate observed was 45.00, 40.00 and 65.00 per cent in groups I, II and III, respectively. The overall conception rate  recorded in Kangayam cow was 50.00 per cent. Based on the findings, it was concluded that liposome based extender may  be used for cryopreservation of Kangayam bull semen in order to maximize the fertility rate.
Keywords: Kangayam; CASA; Kinematics; Conception rate; Extenders